ERROR ANALYSIS OF THE FREE WRITING ESSAYS OF THE SIXTH GRADE ENGLISH LEARNERS AT LABORATORY ELEMENTARY SCHOOL OF STATE UNIVERSITY OF MALANG - INDRIYANA, NOVIE (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Error, Error Analysis, Surface Strategy Taxonomy, and Free WritingEssaysLearning English as a foreign language (FL) in Indonesia is not as easy as flipping hands. It takes a lifelong process and can be very challenging for Indonesian FL learners. In the process of learning a language, making mistakes and errors cannotbe avoided. This study is intended to investigate the learners’ errors in free writingessay made by the sixth grade English learners at Laboratory Elementary School ofState University of Malang using surface strategy taxonomy. These students havebeen exposed to English since they are in the first grade, but in facts, some of themare still having confusion in using the correct words. Thus, the problems of this studyare what errors are found in the free writing essay and the most types of error mostlydone by the sixth grade of English learners at Laboratory Elementary School of StateUniversity of Malang.The method of this study is qualitative approach. This study was carried out at Laboratory Elementary School of State University of Malang. The sample of this study is the 6B International Class Program (ICP) at Laboratory Elementary School of State University of Malang in academic year of 2013/2014. The technique used to analyze the data in this study is error analysis. The steps of analyzing the data started from observing the class, collecting the data, identifying the error, describing the error, explaining the error, and drawing the conclusion.The result shows that there are only three types of error made by sisth grade English learners based on surface strategy taxonomy, with total error of each type of error is omission with 15 errors, addition with 9 errors, misformation with 20 errors, and misordering with 0 errors. Misformation is the error that is mostly done by thelearners.The researcher suggests for the next researchers who want to conduct a similar topic use different theory. The other suggestion is, they can use different research subject of the study, such as employees of a foreign company, and different research object such as listening or reading tasks.